ANTIOXIDANT RESPONSE OF TOMATO TO LATE BLIGHT (PHYTOPHTHORA INFESTANS) INFECTION DEPENDING ON SYMPTOMS INTENSITY - MEDIĆ PAP, Slađana; DANOJEVIĆ, Dario; GLOGOVAC, Svetlana; PEIĆ TUKULJAC, Marijana; ŽIVANOV, Dalibor; PRVULOVIĆ, Dejan (Studia Universitatis Babeș-Bolyai Chemia, 2022)
Late blight (LB) caused by the Phytophthora infestans is a devastating tomato disease, distributed worldwide. Tomato wild species could be a potential source of resistance, however, there are little data about their biochemical response to LB infection. Therefore the aim of the study was to evaluate total phenolic and total flavonoid content and antioxidative activity in the leaves of wild (Solanum pimpinellifolium) and cultivated genotype (Bizon) depending on disease severity. S. pimpinellifolium compared to Bizon was less susceptible and had five times lower disease severity index (11% and 55% respectively). Additionally, during the disease progression wild genotype showed a much slower decrease of total biochemical parameters compared to the cultivated one. Parameters such as total phenolic content (TP), DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging test and ABTS (2,2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid)) radical scavenging activity in the symptomless leaves and the leaves infection 10-25% remained the same in S. pimpinellifolium. The susceptible genotype Bizon had about 40% of leaves with the disease severity 25-50%, and a rapid decrease of all biochemical parameters. A strong negative correlation was observed between late blight infection and biochemical parameters in Bizon, while in S. pimpinellifolium late blight infection negatively correlated only with TP, TF (total flavonoid content) and total antioxidant activity (TAA).